2017
DOI: 10.1039/c6ra26003a
|View full text |Cite
|
Sign up to set email alerts
|

Cyclam te1pa for64Cu PET imaging. Bioconjugation to antibody, radiolabeling and preclinical application in xenografted colorectal cancer

Abstract: te1pa conjugated to an F6 antibody was confirmed to be an interesting alternative to dota for64Cuin vivoPET imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 64 publications
1
40
0
Order By: Relevance
“…When considering a 60% radiochemical yield of 64 Cu-PCB-TE2A-tetrazine ( 7 ), the overall radiochemical yields of 64 Cu-PCB-TE2A-trastuzumab ( 9 ) and 64 Cu-PCB-TE2A-PEG 4 -trastuzumab ( 11 ) from Cu-64 ions were 37 and 44%, respectively. The calculated specific activities of the radioimmunoconjugates were 2.6 ± 0.2 MBq/μg ( 9 ) and 2.8 ± 0.4 MBq/μg ( 11 ), which were superior to the previously reported typical values of 64 Cu-labeled immunoconjugates. , …”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…When considering a 60% radiochemical yield of 64 Cu-PCB-TE2A-tetrazine ( 7 ), the overall radiochemical yields of 64 Cu-PCB-TE2A-trastuzumab ( 9 ) and 64 Cu-PCB-TE2A-PEG 4 -trastuzumab ( 11 ) from Cu-64 ions were 37 and 44%, respectively. The calculated specific activities of the radioimmunoconjugates were 2.6 ± 0.2 MBq/μg ( 9 ) and 2.8 ± 0.4 MBq/μg ( 11 ), which were superior to the previously reported typical values of 64 Cu-labeled immunoconjugates. , …”
Section: Resultsmentioning
confidence: 50%
“…The calculated specific activities of the radioimmunoconjugates were 2.6 ± 0.2 MBq/μg (9) and 2.8 ± 0.4 MBq/μg (11), which were superior to the previously reported typical values of 64 Cu-labeled immunoconjugates. 18,50 We also prepared 64 Cu-NOTA-Bn-NCS-trastuzumab (12) (Figure S30) to directly compare the in vivo stabilities of the antibodies radiolabeled by using the different bifunctional chelators. NOTA is a non-cross-bridged macrocyclic chelator known to form stable copper complexes, and it is widely used as a bifunctional chelator for 64 Cu radiolabeling.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, CB-TE2P shows good labeling with 64 Cu, even at room temperature, although CB-TE2A requires prolonged heating at high temperature. Recently, cyclams with picolinate pendant arm(s) (e.g., TE1PA, Chart ) have been suggested as ligands for efficient radiocopper incorporation. Among ligand skeletons, cyclam-based ligands are known to have the best thermodynamic selectivity for Cu­(II). We have previously shown that Cu­(II) selectivity is preserved in phosphonic acid cyclam derivatives and is associated with the good kinetic inertness of Cu­(II) complexes of these ligands. On the basis of our experience with cyclam phosphonic acid derivatives and on studies on simple geminal bis­(phosphinates), , we have recently designed cyclam-based ligands with one geminal bis­(phosphinate) ( te1bpin ) or geminal phosphino-phosphonate ( te1pp ) pendant arm (Chart ) for fast complexation of Cu­(II) ions .…”
Section: Introductionmentioning
confidence: 99%
“…The C -functionalization strategy was developed to provide a second functionality to the macrocycle, different from the one introduced with N -chelating units . We and others have largely contributed to this chemistry using these derivatives for several applications, especially for the conjugation of the macrocycles to an external support or a targeting moiety. The structural modifications introduced through C -functionalization of the cyclam framework affect the biological properties of the complexes by modifying the lipophilic character of the ligands as well as by directing the complex to the desired target in vivo.…”
Section: Introductionmentioning
confidence: 99%